Pterostilbene inhibits non-small cell lung cancer progression by activating the STING pathway and enhancing antitumor immune response - Kang, Li-Ping; Xie, Han; Huang, Hua-Jing; Xu, Pan; Xu, Cong; Huang, Dong-Hui; Jiang, Ze-Bo (Frontiers in Immunology, 2025)
IntroductionNon-small cell lung cancer (NSCLC) is a leading cause of cancer-related mortality, and current therapies often yield limited efficacy. This study investigated the antitumor potential and mechanisms of Pterostilbene (PTE), a natural stilbenoid with superior bioavailability.MethodsThe antitumor effects of PTE were assessed in A549 and H358 NSCLC cell lines to determine its impact on cell viability, cell cycle, apoptosis, and reactive oxygen species (ROS) generation, using N-acetylcysteine (NAC) to confirm the role of ROS. Key molecular mechanisms were probed via Western blot, siRNA knockdown, and pharmacological inhibition (H-151). The in vivo efficacy of PTE and its effect on the tumor immune microenvironment were evaluated in H358 xenograft and immunocompetent LLC1 murine models.ResultsPTE suppressed cell viability in a concentration- and time-dependent manner, inducing G2/M phase arrest and mitochondrial apoptosis driven by ROS. It triggered DNA damage and activated the STING pathway, leading to TBK1/IRF3 phosphorylation and the secretion of T-cell chemoattractants (CXCL10, CXCL9, CCL5). STING inhibition markedly attenuated PTE's effects. In vivo, PTE suppressed tumor growth and remodeled the tumor microenvironment by increasing granzyme B+, TNF-α+, and IFN-γ+ CD8+ T cells while reducing myeloid-derived suppressor cells and regulatory T cells.DiscussionOur findings elucidate a dual mechanism whereby PTE directly kills NSCLC cells via ROS-mediated apoptosis and simultaneously reinvigorates antitumor immunity through STING pathway activation. This positions PTE as a promising candidate for combination immunotherapy in NSCLC.